2020
DOI: 10.1021/acs.biomac.0c00962
|View full text |Cite
|
Sign up to set email alerts
|

One-Shot Synthesis of Peptide Amphiphiles with Applications in Directed Graphenic Assembly

Abstract: High molecular weight, synthetic block copolypeptides that self-assemble are in high demand for biomedical applications. The current standard method for synthesis of block copolypeptides is the controlled ring-opening polymerization (ROP) of α-amino acid N-carboxyanhydride (NCA) monomers, where block architectures can be created by sequential NCA monomer addition. Recently, researchers have focused on developing reaction conditions and initiation systems that make NCA ROP more convenient, particularly for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…GO solid surfaces—such as thin films or pellets—are unstable in water and redisperse, preventing traditional contact angle measurements. [ 66,67 ] The contact angles of the GO dispersions show minor differences compared to DI water (Figure S2F, Supporting Information). For the increasingly oxidized GO materials, contact angle increases with increasing backbone oxidization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO solid surfaces—such as thin films or pellets—are unstable in water and redisperse, preventing traditional contact angle measurements. [ 66,67 ] The contact angles of the GO dispersions show minor differences compared to DI water (Figure S2F, Supporting Information). For the increasingly oxidized GO materials, contact angle increases with increasing backbone oxidization.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have previously shown that the DLS‐determined Z‐average diameter reasonably agrees with the particle dimensions measured using high‐resolution optical microscopy, atomic force microscopy, and scanning electron microscopy. [ 66–70 ] Thus, for experimentally relevant micron‐sized sheets of GO, settling will dominate.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing interest in the conjugation of antimicrobial peptides with antibacterial graphene-based materials [ 180 ], for instance for potential applications in wound healing. To this end, one-pot ring-opening copolymerization of lysine and leucine N -carboxyanhydride into self-assembling polypeptides was used as a simple strategy to yield self-assembling antimicrobials that were also conjugated to graphene to yield hierarchical structures [ 181 ]. Antibacterial membranes were developed by combining a self-assembling palmitoyl tetrapeptide with GO flakes [ 134 ].…”
Section: Research On the Interaction Between Self-assembling Peptides And Nanocarbonsmentioning
confidence: 99%
“…Zhang provided two efficient ways to synthesize polypeptides from 𝛼-amino acid NTAs in DCM, hexane, and heptane. [79,81] In addition to nonpolar and low polar solvents, amine-initiated NTA polymerizations are also reported to be carried out in polar solvents including DMF [102,80] and THF [9] (Scheme 5vii). However, the researches focus on the preparation and application of PAAs while investigation into the polymerization mechanism and controllability is insufficient.…”
Section: Polymerization Of Ntasmentioning
confidence: 99%
“…The polypeptide amphiphiles assembled into various graphemic materials such as micelle, vesicle, and sheet according the composition of polypeptides. [80]…”
Section: Nta Monomers and Applicationmentioning
confidence: 99%